2011
DOI: 10.1179/030192310x12690127076398
|View full text |Cite
|
Sign up to set email alerts
|

Pilot plant study of nozzle clogging mechanisms during casting of REM treated stainless steels

Abstract: A pilot scale bottom teemed high frequency furnace with a nominal capacity of 600 kg and an adjustable nozzle temperature was used to study clogging of rare earth metal (REM) treated stainless steels. The influence of the following variables on the clogging was studied: amount of REM, fraction of oxide clusters, total oxygen content in the steel, reoxidation, aluminium additions before REM additions and silicon additions during casting. Overall, the results show that, during the present experimental conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(71 citation statements)
references
References 24 publications
3
66
0
Order By: Relevance
“…After experiment, the steel left in ladle must be tapped out making it difficult to get a sample of solidified steel at that region. However, supporting the model results is the comparable experiments reported by Kojola,40) demonstrating that clogging also frequently occurs in the upper part of the nozzle. Both the simulation and experiment show that the transition region of geometry, or flow field, is the sensitive region for an inclusion deposition, as well as for clogging.…”
Section: Inclusion Behavior Including Stochastic Turbulentsupporting
confidence: 81%
See 2 more Smart Citations
“…After experiment, the steel left in ladle must be tapped out making it difficult to get a sample of solidified steel at that region. However, supporting the model results is the comparable experiments reported by Kojola,40) demonstrating that clogging also frequently occurs in the upper part of the nozzle. Both the simulation and experiment show that the transition region of geometry, or flow field, is the sensitive region for an inclusion deposition, as well as for clogging.…”
Section: Inclusion Behavior Including Stochastic Turbulentsupporting
confidence: 81%
“…Although a lot of inclusions exist at the straight pipe nozzle wall, they are not the vital reason for the interruption of teeming. In Kojola et al study,40) clogging at the upper part of the nozzle near the connection region between the nozzle and ladle bottom was also found. …”
Section: Experimental Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in channel 6 the seat is initially heated to a higher temperature in comparison to the other measurement positions. Since the clogging in the seat is the flow limiting factor in the SEN, it is of most importance to have a controlled preheating process [15]. Even though torches in the tundish lid were used, the lower temperature in channel 6, compared to the highest measured temperature, indicates that the temperature contributions from the torches in the tundish lid to the SEN were lower than from the torches at the SEN outlet.…”
Section: The Influence Of Preheating Parameters On Decarburisationmentioning
confidence: 99%
“…1) Further studies [2][3][4][5][6] reported that rare earth metals reduce the degree of undercooling for nucleation, refine the as-cast structure, and limit solidification segregation in steels. However, the addition of a mischmetal to liquid steel often leads to formation of REM clusters and nozzle clogging, [7][8][9] which is a serious problem during continuous casting in the steel industry. Kojola et al 7) found that the main part of the nozzle accretion was caused by agglomeration of Ce inclusions and clusters.…”
Section: Introductionmentioning
confidence: 99%